The degree of organizational loyalty among faculty members at Tishreen University A field study in the theory and practice of colleges in the University of Tishreen - Nayfeh Ali; Muhannad Moubayed; Mais Jawdat Aziza (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aims to find out the organizational loyalty score among faculty members at Tishreen University, as well as determine if there was a statistically significant differences between them due to the variable gender and college and their top managerial position and scientific ranks, study sample consisted of 90 members, has been using the questionnaire as a tool to collect data, and results it showed that there is an average of organizational loyalty among faculty members, and the lack of a statistically significant difference between faculty members to identify organizational loyalty degrees by gender variable and he held a managerial position level, while there was a difference between them as a variable of type College for the benefit of colleges theory and the existence of differences by variable Grade favor of assistant professor.